ORGANIZATION OF PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT OF UNIVERSITY ENTRANTS - Nikolay A. Petrov; Dar’ya A. Troeshestova (Высшее образование в России, 2016)
The article examines the necessity, goals and tasks ofpsycho-pedagogical support of university entrants in the continuing education system. The functional two-stage model of psychological and pedagogical support of university entrants is offered. The testing results of this model in the period of admission campaign 2014 of the Chuvash State University are submitted for discussion.